Wybór spikera brytyjskiej Izby Gmin w świetle prawa, zwyczajów i praktyki parlamentarnej - Urbaniak, Krzysztof (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
Speaker of The House of Commons is one of the most important offices in the British parliamentary system. The political status of this office has been subject to evolution since the 14th century and it has been shaped by numerous customs and the Chamber's practice. On the basis of this, a model of independent and impartial parliamentary leadership was formed. Certainly, the rules for the selection of the Speaker are among the most important elements affecting the position of the Speaker. These rules have been fundamentally changed in the last decades. The subject of this study is the analysis of the evolution of the principles of election and its impact on the principle of political independence and impartiality of the Speaker.
Keywords: speaker; secret ballot; House of Commons; election